Edukasi Penerapan Manajemen Keuangan Keluarga Syariah Untuk Mengelola Pengeluaran Dan Meningkatkan Tabungan Keluarga Pada Komunitas Ikatan Keluarga XIII Koto Kampar Sadayoung - Rahmawati, Rahmawati; Assyifa, Zubaidah; Mairiza, Diany; Delia, Dwi Anisa; Maini, Nur (EL-EMIR INSTITUTE, 2025)
This community service activity was carried out for the Ikatan Keluarga XIII Koto Kampar Sadayoung Community in Bangkinang, Riau Province, where the purpose of this community service was to provide a provision of understanding regarding the application of sharia family financial management to manage expenses and increase family savings in the Ikatan Keluarga XIII Kota Kampar Community in Bangkinang. The methods used in this community service activity are through counseling and presentations, discussions and exercises for participants. The counseling method is used to explain the importance of knowing the application of sharia family financial management to manage expenditure levels and increase savings. The presentation method is used to show a work process, namely the stages of how to become a person who has a prosperous economy according to sharia principles. Meanwhile, the question and answer method is used to provide opportunities for community bond participants to consult in understanding further the material that has been explained. The exercise method is used to see the level of understanding of the service participants before and after the material is delivered. The availability of adequate experts in delivering this material, the enthusiasm of the participants, the support of the head of the community bond for the implementation of the activity are supporters of the implementation of this PkM activity. The obstacles faced were that the community service participants did not yet have initial knowledge about the material on Islamic family financial management and time constraints in delivering the material. The results of this community service show that: The community service program can be organized well and run smoothly according to the activity plan that has been prepared, the results of this community service concluded that: First, Most community service participants do not yet understand Islamic family financial management well, Second, The achievement of the objectives of the community service program for community service participants, the entire program that has been carried out with collaboration between the community and the community service has been carried out all and in accordance with the event rounddown and the time that has been determined previously.